2005
DOI: 10.1097/00005131-200501000-00008
|View full text |Cite
|
Sign up to set email alerts
|

An Alternative Method of Osteosynthesis for Distal Humeral Shaft Fractures

Abstract: Treatment of extra-articular distal humerus shaft fractures with plating techniques is often difficult, as traditional centrally located posterior plates often encroach on the olecranon fossa, limiting distal osseous fixation. The use of a modified Synthes Lateral Tibial Head Buttress Plate (Synthes, Paoli, PA) allows for a centrally placed posterior plating of the humeral shaft that angles anatomically along the lateral column to treat far distal humeral shaft fractures. Fifteen patients treated in this manne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 8 publications
1
54
0
1
Order By: Relevance
“…Indeed, in clinical practice it is not common to place the plates and so many screws so distally in extra-articular fractures of the distal humerus. [2][3][4][5][6][7]10,11 This study suggests that under physiological loads, which are common in the immediate postoperative period, the largest displacements on the joint surface are observed on the radial condyle, and the largest displacements in the gap area are observed in the front part. This information suggests that it is necessary, regardless of whether one or two plates are being placed, to achieve greater stability in the radial column area, which was also confirmed in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, in clinical practice it is not common to place the plates and so many screws so distally in extra-articular fractures of the distal humerus. [2][3][4][5][6][7]10,11 This study suggests that under physiological loads, which are common in the immediate postoperative period, the largest displacements on the joint surface are observed on the radial condyle, and the largest displacements in the gap area are observed in the front part. This information suggests that it is necessary, regardless of whether one or two plates are being placed, to achieve greater stability in the radial column area, which was also confirmed in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…This information suggests that it is necessary, regardless of whether one or two plates are being placed, to achieve greater stability in the radial column area, which was also confirmed in clinical practice. 2,4 The significance of lateral column stabilization is all the greater if we know that in the case of osteoporosis in the distal humerus region, it is most pronounced in the posterolateral segment. 28,29 Moreover, it was found that the cortex in the medial column region is substantially stronger in comparison with the lateral column, both in the supra-and infracondylar region of the distal humerus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3,8,9,[16][17][18][19][20][21][22][23] Algunos autores comunican similares resultados entre la TMI y la cirugía convencional con placas y tornillos. 24 La osteosíntesis abierta con placas de compresión está considerada entre los mejores métodos de tratamiento.…”
Section: Discussionunclassified